Determination of Maiganga Lignite Coal Combustion Characteristics for Application in Thermal Power Plant using Standard Mathematical Models - Ozigis, I. I.; Zarmai, M. T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This paper presents determination of Maiganga lignite coal combustion characteristics for application in thermal power plant using standard mathematical models. The problem statement was that Nigeria cement plants uses rotary kiln coal burner despite its associated drawbacks such as sudden explosion and incomplete combustion. Fluidized bed technology has less of the drawbacks associated with rotary kiln coal burner. The integration of Maiganga coal in mathematical models will increase accurate prediction of operating variables useful in design and sizing the components of fluidized bed thermal power plant. The methodology of the study includes utilization of established numerical models based on energy balance and fuel properties for Maiganga lignite combustion. The coal was fired in a pilot atmospheric fluidized bed combustor (FBC). The results obtained include the theoretical air required per kg of Maiganga lignite was 7.4, at an excess air of 10% and maximum mass of air supplied per kg of Maiganga lignite of 8.82. The time for burn out of particle sized 0.4 mm was determined to be 2.64 min, with burning rate of 0.23 kg/min (3.8 g/s). The ignition temperature of 797 K and fuel power of 84 kW for Maiganga coal were determined for the pilot FBC in this study. The Maiganga lignite fuel, air and sorbent flow rates through the fluidized bed combustor were predicted to be 14.2 kg/hr (0.23 kg/min), 202.4 kg/hr and 1.26 kg/hr respectively. The combustion performance evaluation of the fluidized bed combustor had specific firing rate for the lignite at graded particle size of between 0.2-1.12 mm at bed temperature of 1173 K was 2.8 g/m2s, air-fuel ratio of 23 and equivalence ratio of 0.45. The above results are similar to coal burnout time of 3 minutes and equivalence ratio of 0.40 in an atmospheric fluidized bed combustor in the literature. Hence, above parameters can be used to design and model a safe ignition and good combustion characteristics in other lignite fired power plants similar to that of Maiganga lignite coal.